2020
DOI: 10.3390/coatings10100960
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Morphologies Governed by the Competition of Viscous Dissipation and Phase Separation in a Radial Hele-Shaw Flow

Abstract: The displacement of a less viscous fluid by a more viscous fluid in a radial Hele-Shaw cell makes a circular pattern because the interface is hydrodynamically stable in this condition. Very recently, it has been experimentally reported that the hydrodynamically stable displacement in a partially miscible system induces fingering patterns while stable circular patterns are made at fully miscible and immiscible systems. The fingering instability in the partially miscible system results from complex and entangled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…6 we show the interfacial tension measured by the spinning method and denoted as , where the subscript m 𝜸 𝒎 indicates "measured". The previous report showed that the temporal increase of interfacial tension was evidence for occurrence of the Korteweg force 12,19,20 . In Fig.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…6 we show the interfacial tension measured by the spinning method and denoted as , where the subscript m 𝜸 𝒎 indicates "measured". The previous report showed that the temporal increase of interfacial tension was evidence for occurrence of the Korteweg force 12,19,20 . In Fig.…”
Section: Resultsmentioning
confidence: 94%
“…19 Partially miscible systems have also been reported experimentally to show anomalous patterns because of the phase separation. 20,21 Numerical simulations by Seya et al 22 reproduced such multiple-droplet formation with a partially miscible system.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies regarding interfacial hydrodynamics that considered fully miscible and immiscible cases have been reported [3,[9][10][11][12]. Recently, Suzuki et al discovered a novel interfacial dynamics feature using a partially miscible system, which can be treated at room temperature and atmospheric pressures [13][14][15][16]. Their partially miscible system was comprised of polyethylene glycol (PEG), Na 2 SO 4 , and water, for which spinodal decomposition phase separation occurred at the boundary of the displacing and displaced liquids.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1. Phase diagram of the polyethylene glycol (PEG)-Na 2 SO 4 -water system[15]. The different color symbols show the three systems having different three thermodynamic states: the red circles for the immiscible system, the blue circles for the fully miscible system, and the green circles for the partially miscible system.…”
mentioning
confidence: 99%